2019
DOI: 10.1155/2019/8647587
|View full text |Cite
|
Sign up to set email alerts
|

Nanobubbles Water Curcumin Extract Reduces Injury Risks on Drop Jumps in Women: A Pilot Study

Abstract: Purpose. To verify the beneficial effects of Nanobubbles water curcumin extract (NCE) supplementation on health promotion and to demonstrate the application of NCE in reducing the risk of musculoskeletal injury. Methods. In the current study, 12 females were randomly assigned to NCE (15g/day) and maltodextrin groups. Performance and related body composition were evaluated at 2 time points—presupplementation (pre-) and after 4 weeks of postsupplementation (post-). The posttest consists of a set of biochemical p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 13 publications
(23 citation statements)
references
References 37 publications
2
21
0
Order By: Relevance
“…Thus, the higher ALT concentration in the LFP would agree with some results that suggest the lack of estrogen's protective effect, but further investigation is warranted. On the contrary, the AST response was not affected by menstrual cycle phases but increased in post-exercise measurements, which is in accordance with previous female studies [43,44].…”
Section: Discussionsupporting
confidence: 92%
“…Thus, the higher ALT concentration in the LFP would agree with some results that suggest the lack of estrogen's protective effect, but further investigation is warranted. On the contrary, the AST response was not affected by menstrual cycle phases but increased in post-exercise measurements, which is in accordance with previous female studies [43,44].…”
Section: Discussionsupporting
confidence: 92%
“…The sample size ranged from 12 to 28 individuals. As for the study sites, three of them were conducted in Japan [ 2 , 3 , 20 ], one in China [ 21 ], and one in the United States [ 22 ]. All studies were randomized and controlled.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, most studies ( n = 3; 60%) observed that treatment with curcumin could reduce CK activity, showing the benefits of curcumin supplementation in reducing pain and muscle damage by decreasing CK. Serum CK is an important clinical biomarker for muscle damage, such as muscular dystrophy, severe muscle destruction, and a marker of peripheral fatigue during physical exercises [ 21 , 22 ]. In addition, most studies ( n = 4; 80%) evaluated muscle pain; two of these (50%) reported a reduction in muscle pain.…”
Section: Resultsmentioning
confidence: 99%
“…Data Collection. Twenty-one reflective markers (19 mm in diameter) were attached to anatomical landmarks on the legs and pelvis to define a seven-segment rigid link model of the lower extremities, according to the Helen Hayes marker set [27]. The three-dimensional (3D) trajectories of the reflective markers on the participants were collected with 10 cameras (BTS DX400, BTS Bioengineering, Milano, Italy) at a sampling frequency of 200 Hz.…”
Section: Methodsmentioning
confidence: 99%